Design of an impeller of Pelton turbine - Tóth, Dániel; Bozzay, Péter (Design of Machines and Structures, 2025)
Pelton turbine impeller (often called Pelton wheel or Pelton runner) is the main rotating component of a Pelton turbine, which is a type of impulse water turbine used to generate electricity from high-head, low-flow water sources. The Pelton turbine operates on the impulse principle; water jet strikes the buckets of the runner and the change in momentum of the water jet produces a force that causes the runner to rotate. This article focuses on designing procedures to improve a damaged Pelton impeller.